RATIO DECIDENDI MAHKAMAH AGUNG MEMBATALKAN PUTUSAN JUDEX FACTIE DAN MENGADILI SENDIRI DALAM PERKARA NARKOTIKA - Ardelia, Ivana Gisela; Rustamaji, Muhammad (Sebelas Maret University, 2023)
This research aims to find out the ratio decidendi of the Supreme Court which annulled the Judex Factie’s decision and made judgment on own authority in a narcotics crime case in accordance with Article 256 jo. 255 of the Criminal Procedure Code. This research is aimed at examining the application of criminal procedural law to the Supreme Court Decision Number 4043K/Pid.Sus/2020 which in its decision annulled the Judex Factie’s decision and made judgment on own authority in a narcotics crime case. This type of research is normative research that is prescriptive and applied with a case approach. The legal materials used are primary and secondary legal materials, while the technique of collecting primary and secondary legal materials used is literature study. Based on the results of the discussion, that the ratio decidendi in Supreme Court Decision Number 4043K/Pid.Sus/2020 which annullled the Judex Factie’s decision and made judgment on own authority in accordance with the provisions of Article 256 jo. Article 255 KUHAP. This is because the Defendant was not legally and convincingly proven guilty of committing a crime as charged in the first or second indictment of the Public Prosecutor.Keywords: Cassation Defendant; Narcotics; Ratio Decidendi